A COMPREHENSIVE OVERVIEW AND ANALYSIS ON TRAINING AND CERTIFICATION STANDARDS FOR MEDICAL DEVICE TECHNICIANS - 1Saleh Ali Saleh Al Mubti, 2Abdullah Salem Alqaoud, 3Ahmed Husain Hasan Al Hashwan, 4Mohammed Abdullah Alzamanan, 5Hassan hamad Al hafshan, 6Mohammad Abdullah Mohammad Alfaifi, (Chelonian Research Foundation, 2022)
This paper provides a comprehensive overview and analysis of training and certification standards for medical device technicians. The significance of guaranteeing technicians have the essential abilities and information to function and work restorative gear securely and successfully cannot be thought of. Through a subjective writing audit, methodological survey, and discourse, this article centers on current patterns, distinguishes crevices, and offers proposals for making strides in training and certification preparation. The most recent discoveries are that designs shift over districts and segments, illustrating the need for collaboration and ceaseless change of work. Proposals incorporate setting up successful capacity-building and regular preparation programs to guarantee the most noteworthy levels of patient safety and gear performance. Keywords: medical device technicians, training, certification standards, competency, patient safety.